THE EXCITATION OF WAVES IN MECHANICAL OSCILLATION SYSTEMS FOR DISCOVER THEIR PROPERTIES USING THE SPECTRAL IMPEDANCE - Стрілецький, Юрій Йосипович; Дунець, Роман Богданович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The method of research of mechanical vibrational systems with distributed parameters according to their spectral impedance, which is sought by the ratio of the signals of the force of force to the speed of displacement, is proposed. Are developed the method of adaptive adjustment of the signal of excitation force using a random noise signal, by analyzing the system's response to this excitation and increasing its influence.